AB0213 A Stabilised-Release Neuropeptide Functions as A Novel Cutaneous Anti-Fibrotic Agent. (10th June 2014) - Woloszynek, J.; Etzel, K.; Vernes, J.; McIntosh, D.; Moore, C.; Haq, M.; Lopez, H.; Haq, S.
Abstract : Background: Stabilized-release caprine corticotrophin releasing hormone-1 (SR-CCRH-1) is held in a multi-protein complex and derived from hyperimmune caprine sera (HICS). SR-CCRH-1 may have an efficacy trait and accordingly warranted investigation. Objectives: The objective of the study was to determine whether a novel stabilized-release caprine corticotrophin releasing hormone-1 (SR-CCRH-1) neuropeptide could elicit measurable efficacy as an anti-fibrotic agent in the murine bleomycin (BLM)-induced skin fibrosis model (an in vivo study model used to demonstrate the therapeutic effects of test articles on cutaneous fibrosis and inflammation). Methods: For this study, age-sex-matched C57BL/6 male and female mice, n=8-12 per treatment group (saline control, naïve serum control, bleomycin/saline, bleomycin/naïve and bleomycin/SR-CCRH-1), were injected daily with (100 μg s.c.) of SR-CCRH-1 or naïve serum in the respective group using a double-blind experimental protocol for 50 days. Study mice were administered with 0.09 units of BLM in 50 μl volume by s.c. injection on alternate days for 50 days. Results: The results showed that on examination of immunohistochemical staining of skin biopsies [taken from sections from each group (n=6)] using H&E, Masson's Trichrome, a-skeletal muscle actin and thrombin, that SR-CCRH-1 significantly inhibited cutaneous fibrosis (p<0.05), inflammatory cellular infiltrate (p=0.051), epidermal thickening (p=0.012) and reduced ulcer formation marginally (p=0.093) in the BLM/SR-CCRH-1 group relative to control groups. ELISA studies from skin homogenates further confirmed and showed that SR-CCRH-1 significantly reduced the hydroxyproline content (p=0.0133) and lipoprotein related peptide-1 (p=0.009) levels in the skin of animals treated with BLM. A significant increase in a-melanocyte-stimulating hormone (p=0.003), a cleavage product of pro-opiomelanocortin was also noted. The mechanism of action appeared to revolve around a CRH-1- (p=0.0027) and not CRH-2-mediated response. Skin homogenates showed that MC-4R a target of a-MSH (but not MC-1R) appeared to be significantly involved as a downstream target (p=0.017). MMP-9 (p=0.019), MMP-1 (p=0.058), MMP-13 (p=0.038) and PIIINP (p<0.05) were also significantly reduced in the SR-CCRH-1 treated BLM mice vs BLM-treated controls. ELISA studies on serum taken from the study groups further confirmed significant inhibition of MMP-9 (p=0.0291) and a change in TIMP1 (p=0.058). Conclusions: The study taken together provides a novel targeted approach that focused on the CRH-1 receptor expressed in the skin and hypothalamo-pituitary-adrenal axis that led to a cascade of changes highlighted by abrogation of inflammation and cutaneous fibrosis. SR-CCRH-1 may serve as a potential therapeutic in the treatment of cutaneous fibrotic disease. To that end, in a recently completed phase II double blind placebo controlled trial in established late-stage diffuse systemic sclerosis using SR-CCRH-1 pointed to an efficacy signal with reduced a Modified Rodnan Skin Score, and a favourable safety/tolerability profile. Disclosure of Interest: J. Woloszynek: None declared, K. Etzel: None declared, J. Vernes Employee of: employee, D. McIntosh Shareholder of: Shareholder, Consultant for: Consultant, C. Moore Shareholder of: Shareholder, M. Haq Shareholder of: Shareholder, H. Lopez: None declared, S. Haq Shareholder of: Director DOI: 10.1136/annrheumdis-2014-eular.5868